Las redes sociales y su incidencia en el comportamiento de los estudiantes del tercer año de bachillerato de la Unidad Educativa Clemente Baquerizo de la Provincia de Los Ríos, cantón Babahoyo, periodo lectivo 2019 - Zúñiga Contreras, Welligton Rubén (2019)
Education technologies are no longer an option because they provide learning methods and are part of the life of the current generation and for this reason they must work in favor of learning, so it is concluded to apply a didactic manual because one of the best options to help know the benefits of technologies, as well as the effects produced by the misuse of social networks in third year high school students of the Educational Unit "Clemente Baquerizo", Canton Babahoyo, Province from the rivers. With the result of the surveys that were applied to teachers and students, it is determined that teachers do not know all the benefits of technologies, and that students use social networks inappropriately, generating conflicts in the aforementioned educational institution; ICTs are of great importance in education as long as there is a correct guide to their use, so as not to generate inappropriate behavior or virtual violence such as cyberbullying. The teaching manual is a novel teaching methodologies; because it can be used in print or digital form adapting to the current conditions presented by society and the educational community in general, allowing more interactive among teachers-students and thus creating new experiences that help students have learning significant and appropriate behaviors to the ethics and morals that must be had in society.